O silêncio de Narciso : uma leitura sobre as implicações do espetáculo e do simulacro no narcisismo contemporâneo - Correia, Rômulo Marcelo dos Santos (2012)
This work starts with a reading of contemporary ideas based largely on the Society of the Spectacle, of Guy Debord, and the world governed by the simulacra, of Jean Baudrillard, and its implications for a fundamental constituent of the psyche: the narcissism. For this, we begin with a definition of the concept of narcissism in the text of Sigmund Freud, with the importance of this stage is in the formation of Ego and the establishment of the place of otherness and relations with the world. Then, we explain the main ideas about the spectacle in Debord's text, and simulacra, in some texts of Baudrillard, characterizing them and discussing such ideas with the contemporary. Finally, we try to establish points of contact or seek to understand the possible influence that the shows and exercises are in the way it is currently constituted narcissism. To cope with this task, use some authors who have thought nowadays, the main one being André Green, and his idea of negative narcissism. Thus, this narcissism that we find in the shadow of the spectacle and the simulacrum has complications relating to: an Ego ideal weakened in favor of an ideal Ego highly linked to consumerism; a spectacular view of the imperative that Ego should be better than the [of] others; and an experience of the body as another object to be exchanged. Such changes in narcissism showed a decrease of its influence by Eros and the life‟s instincts to an increasing predominance of Thanatos and death‟s instincts.